Fracture Stregnth of Endodontically Treated Teeth with Minimally Invasive Access Cavity Desgins Versus Conventional One (An In Vitro Study) (Indian Journal of Public Health Research & Development, 2021)
Aim: Assess the fracture strength of endodntically treated teeth with minimally invasive access cavitydesign versus conventional one.Methods: Forty four extracted molars were assigned to 4 groups. Conservative Access Cavity, Ninja AccessCavity, Truss Access Cavity, Traditional Access Cavity (n = 11/group/type). Teeth in the Traditional groupwere prepared following the principles of traditional endodontic cavities. Conservative access prepared byusing 2 periapical radiographs to determine canals location. Ninja access scans were plotted on cone beamcomputed tomographic images for localization of root canal orifices and Truss group were scanned, andmerged with cone beam computed tomography, for fabrication of an endodontic guide.The 44 specimenswere loaded to fracture in a universal material testing machine. The maximum load at which the teethfractured and fracture pattern (restorable or unrestorable) were recorded.Results: Regarding the fracture strength, results showed that there was a significant difference betweenNinja, Conservative,Truss and traditional access groups with (p < 0.001) and no significant differencebetween Conservative and Truss groups. Regarding restorability, there was no statistical difference observedbetween the four groups with (p < 0.001).Conclusion: Teeth with traditional access showed lower fracture strength than the ones prepared withConservative, Ninja and Truss.
Keywords: conservative access ,fracture resistance, ninja, traditional access ,truss.